Identifying ground displacement trends in Bucharest using InSAR - Iuliana Armas; Mendes, D. A.; Popa, R.G.; Popovici, D.; Diana Gheorghe (The 33rd ROMANIAN GEOMORPHOLOGY SYMPOSIUM, 2017)
Some of the most popular multi-temporal interferometric techniques used in monitoring surface movements have been applied for capturing the spatial evolution patterns of Bucharest. Three sets of C and X-band single polarized SAR images (Envisat, ERS and TSX) were processed using the PS (Persistent Scatterers) and SBAS (Small BAseline Subset) techniques. The processing results consisted of deformation maps offering an image of the line of sight displacement rates in the past. In both PS and SBAS cases, displacement rates values are of the orders of millimetres. The analysis of possible trends is focused on relevant areas with a potentially interesting historical evolution, such as former clay pits, landfill excavation sites and industrial platforms. The InSAR techniques made it possible for the first time to investigate movements over large urban areas in combination with results derived from classical methodologies (diachronic cartography, geology, geomorphology) and thorough statistical analysis. The analyses lead to a new hypothesis regarding the geological processes that affect the surface evolution patterns in Bucharest.